Transit to nowhere: how Sub-Saharan African migrants in Morocco confront life in forced immobility - Stock, Inka (2013)
This thesis is based on an ethnographic study of the lives of Sub-Saharan African migrants residing in Morocco. Over the past two decades, an increasing number of these migrants live in the urban centres of the country, mostly without migration status and with very limited access to formal employment, social services and legal protection. While many of these migrants wish to move on to another country, return to their home countries or, in some cases, settle permanently in Morocco, most are unable to do so and are 'stuck' in a situation of 'forced immobility' for indeterminate periods of time.